Automatic whiteboard eraser - Samion, Norhafiza; Syukri, Nur Nisha Camelia; Hasramani, Nur Uzma Afrina; Tamin, Nik Nur Faiqah (Penerbit UTHM, 2020)
Whiteboard erasing is a common or a must do for teachers or students especially in learning. Other than that, the significance of the project is to make the erasing or cleaning process a lot easier and saves times that can meet the demands of certain groups as well as to achieve the project’s objective. It was observed that the method that is widely or commonly used is writing process through the whiteboard because it is more effective. There are various problems that often occur among students and teachers when erasing whiteboards especially in universities or in schools which it takes a while to erase what teachers or students have written on the whiteboard and to write something new. For example, Universiti Tun Hussein Onn Malaysia itself faced a lot of problems regarding this matter such as the erasers or duster are always went missing because it was put recklessly and worn out easily so this this requires the lecturers or students to bring their own dusters or use other alternatives such as using a cloth or tissues. The whiteboard size at universities and schools also plays an important role as most of the whiteboards are large and it takes a lot of time to clean the whole whiteboard surface.